Comparative analysis of good governance patterns in rural areas (Case study: villages in the central part of Pol-e Dokhtar county and Musaian section in Dehloran county) - Farzad Karami; Hamid barghi; yousof ghanbari (تحقیقات کاربردی علوم جغرافیایی)
Good governance, having the most important principles and criteria for public participation, accountability, accountability, centralism, transparency, efficiency and effectiveness, justice and equality, consensus and legitimacy is one of the new management approaches and new approaches to development and poverty reduction, especially poverty. This study aimed was to conduct a comparative analysis of the goog governance model in rural areas with an emphasis on the villages of the central part of Poldakhtar and Mosian section of Dehloran. The statistical population of the study, according to Cochran's formula, is 284 heads of households living in the villages of the two central parts and Mosian. Inferential data analysis was performed using t-test, and the sample villages were ranked in terms of rural governance status using The Topsis method. The results obtained from The Topsis method show that the governance situation in Mosian section of Dehloran Township is better than the central part of Poldakhtar Township, and the one sample t-test showed that the average of all components of rural good governance is above average and their significance level is an amount less than 0.05. The results of Levin test also show that there is a significant difference between the two central parts and Mosian regarding governance and its components, apart from responsibility (±1/96). Furthermore, In Mosian section, the average components (participation, accountability, and transparency) were higher than the central part of Poldakhtar Township and in the components (legality, collective agreement, justice, efficiency, and effectiveness) were less than the central part of Poldakhtar Township.